Pediatric low-grade gliomas: implications of the biologic era - Packer, Roger J.; Pfister, Stefan; Witt, Olaf (Neuro-Oncology, 2016)
For the past decade, it has been recognized that pediatric low-grade gliomas (LGGs) and glial-neuronal tumors carry distinct molecular alterations with resultant aberrant intracellular signaling in the Ras-mitogen-activated protein kinase pathway. The conclusions and recommendations of a consensus conference of how best to integrate the growing body of molecular genetic information into tumor classifications and, more importantly, for future treatment of pediatric LGGs are summarized here. There is uniform agreement that molecular characterization must be incorporated into classification and is increasingly critical for appropriate management. Molecular-targeted therapies should be integrated expeditiously, but also carefully into the management of these tumors and success measured not only by radiographic responses or stability, but also by functional outcomes. These trials need to be carried out with the caveat that the long-term impact of molecularly targeted therapy on the developing nervous system, especially with long duration treatment, is essentially unknown.
Gesehen am 03.05.2018